Pre-services biology teachers: correlation of metacognition awareness with the ability to design experiments through vee diagram - H Handayani; Rahma Widiantie (Biosfer: Jurnal Pendidikan Biologi, 2020)
Practice plays a role in explaining theory through the form of laboratory activities. Practice in the form of investigation, such as designing experiments, is a form of practice that focuses on the thought thinking process compared to the verification practice. Designing experiments in the form of the Vee diagram are a practice that develops the thought process and metacognition awareness, and it has been one of the factors associated with design experiments. This study aimed to analyze the correlation of metacognition awareness towards the ability to design experiments that are outlined in the form of a Vee Diagram. The method used was correlational research that measured the relationship between metacognition awareness indicators. It consisted of declarative knowledge, procedural knowledge, limited knowledge, and cognition regulation with the ability to design experiments. The sampling technique used purposive sampling with 28 students of the third semester of a private university in Kuningan. Instruments in this study consisted of the Vee Diagram rubric and the Metacognitive Awareness Inventory (MAI) for metacognition awareness. The results showed that there was a correlation between declarative knowledge, procedural knowledge, limited knowledge, and cognition regulation simultaneously with the ability to design experiments by 63.4%. The remaining 36.6% came from other factors.